2001
DOI: 10.1073/pnas.071516798
|View full text |Cite
|
Sign up to set email alerts
|

Pendrin, encoded by the Pendred syndrome gene, resides in the apical region of renal intercalated cells and mediates bicarbonate secretion

Abstract: Pendrin is an anion transporter encoded by the PDS͞Pds gene. In humans, mutations in PDS cause the genetic disorder Pendred syndrome, which is associated with deafness and goiter. Previous studies have shown that this gene has a relatively restricted pattern of expression, with PDS͞Pds mRNA detected only in the thyroid, inner ear, and kidney. The present study examined the distribution and function of pendrin in the mammalian kidney. Immunolocalization studies were performed using anti-pendrin polyclonal and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

30
537
1
11

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 494 publications
(595 citation statements)
references
References 48 publications
30
537
1
11
Order By: Relevance
“…Another candidate for apical Cl -uptake/base secretion is pendrin (SLC26A), which is localized in the apical region of B-type intercalated cells of the cortical collecting duct and which functions in renal Cl -reabsorption and bicarbonate secretion (Royaux et al, 2001;Wagner, 2007). In the stingray (Dasyatis sabina), Piermarini and coworkers (Piermarini et al, 2002) used an anti-pendrin (SLC26A4) antibody to indicate immunoreactions in the apical region of gill ionocytes that are rich in basolateral H + -ATPase.…”
Section: Pendrinmentioning
confidence: 99%
“…Another candidate for apical Cl -uptake/base secretion is pendrin (SLC26A), which is localized in the apical region of B-type intercalated cells of the cortical collecting duct and which functions in renal Cl -reabsorption and bicarbonate secretion (Royaux et al, 2001;Wagner, 2007). In the stingray (Dasyatis sabina), Piermarini and coworkers (Piermarini et al, 2002) used an anti-pendrin (SLC26A4) antibody to indicate immunoreactions in the apical region of gill ionocytes that are rich in basolateral H + -ATPase.…”
Section: Pendrinmentioning
confidence: 99%
“…Pendrin consists of 780 amino acids with a predicted cytoplasmic amino terminus and 12 transmembrane spanning regions (1,2). Functional studies show that pendrin mediates electroneutral exchange of Cl 2 with various anions including I 2 , HCO 3 2 , OH 2 , NO 3 2 , SCN 2 (thiocyanate), and HCO 2 2 (formate) (2)(3)(4)(5)(6)(7)(8). In addition to the inner ear and thyroid, pendrin is expressed in the kidney, airways, and adrenal gland (1,4,6,7,(9)(10)(11)(12).…”
mentioning
confidence: 99%
“…In the thyroid pendrin is expressed on the apical membrane of follicular cells, where it facilitates I 2 efflux into the follicle colloid for thyroid hormone synthesis (2,15). In the kidney pendrin is expressed in the apical plasma membrane of type B and non-A/non-B intercalated cells, where it facilitates Cl 2 absorption and HCO 3 2 secretion, ABBREVIATIONS: ASL, airway surface liquid; CaCC, calcium-activated chloride channel; CF, cystic fibrosis; CFBE, human cystic fibrosis bronchial epithelial; CFTR, cystic fibrosis transmembrane conductance regulator; ENaC, epithelial sodium channel; EYFP-HIF, enhanced yellow fluorescent protein-H148Q/I152L/F46L; FRT, Fischer rat thyroid; HBE, human bronchial epithelial; IC 50 , drug concentration causing 50% inhibition; I sc , short-circuit current; PCL, periciliary layer; UCSF, University of California, San Francisco; YFP, yellow fluorescent protein although kidney abnormalities are rare in Pendred syndrome (4,6,16).…”
mentioning
confidence: 99%
“…More recent studies showed that the apical Cl:HCO 3 exchanger is pendrin (Slc26A4) 9,10 ; hence, we have had to revise our initial hypothesis by saying that acidosis reverses the polarized distribution of only the H ϩ -ATPase, removes pendrin from the apical membrane, and induces the expression of AE1 protein and apical endocytosis.…”
Section: Urinary Acidification In the Cortical Collecting Tubulementioning
confidence: 99%